Estudio exploratorio de la calidad de agua del sistema de riego Chambo – Guano de la provincia de Chimborazo - Lizeth Ivonne, Ponce Tualombo (2020)
Irrigation management in Ecuador implies a great diversity of actors linked to the use of water resources, according to information from the National Irrigation Plan for 2002, the potential irrigation area is 3,1 million hectares representing 30 % The objective of this research was to carry out an exploratory study of the water quality of the Chambo - Guano Irrigation System of the Chimborazo province of extracted water at 10 sites located along the canal. Physicochemical and bacteriological analyzes such as: dissolved oxygen, total coliforms, pH, biochemical oxygen demand, nitrates, temperature, total dissolved solids, cations and anions were performed. From the samples analyzed, the electrical conductivity varied 0,10 – 0,3 dSm-1. The average concentration of Ca2 +, Mg2 +, Na + and K + was 0.20; 0,5; 1,0 and 0,02 cmol L-1, respectively. CO32-, HCO3- average 10 cmol L-1 was not detected. The concentration of Cl- 0,2 cmol L-1, SO4- 0,04 cmolL-1 and NO3- 0,008 cmol L-1 were very low. The pH values have an average value of 7,0 and the RAS has an average value of 5,5 except for the P1 Bocatoma-Ceceles sampling point that has a value of 15,5 RAS. All these values are within the permitted values, for this reason these waters can be classified as suitable for irrigation. However, it is recommended to perform analyzes on soils that are using water from this irrigation system every one or two years.